Green tax reform and two-component unemployment: Double dividend or double loss? - Max Albert; Jürgen Meckl (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1999)
The double-dividend argument (as used in political debates) addresses worries that a green tax may lead to higher unemployment when wages are inflexible. As protection against this possibility, it is proposed to use the proceeds of the green tax to subsidize employment. In the best case, this protects the environment and reduces unemployment (double dividend). However, even if the main cause of unemployment is a minimum wage, an additional efficiency-wage component (which explains certain stylized facts) can dominate employment effects. In the worst case, this leads to a double loss, which is impossible under pure minimum-wage unemployment.
Keywords: J30; Q28; 330; double dividend; efficiency wages; green tax reform; unemployment